PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN SUPERVISI AKADEMIK MELALUI IKLIM SEKOLAH TERHADAP KINERJA GURU DI KOTA SEMARANG - Dwi Lestari; Sungkowo Edy Mulyono; Fakhruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The study aims to determine the simultaneous effect of principal leadership, academic supervision and school climate on teacher performance. Quantitative research method with primary data. The research population was all elementary school teachers in Semarang City.Data collection techniques using questionnaires. Data analysis techniques with Cronbach alpha which includes validity test, reliability test, Three Box Method analysis and SEM PLS analysis. The results of the study statistically showed that the effect of School Climate on Teacher Performance was significant with a p value <0.05, T statistics> 1.96, and a positive path coefficient of 0.326. The effect of Academic Supervision on School Climate is significant with a p value <0.05, T statistics >1.96, and a positive path coefficient of 0.446. the effect of Academic Supervision on Teacher Performance is significant with a p value <0.05, T statistics >1.96, and a positive path coefficient of 0.206. The indirect effect of Principal Leadership on Teacher Performance through School Climate shows a significance of 0.130 with a path coefficient of 0.130, the p value obtained <0.05. The indirect effect of Academic Supervision on Teacher Performance through School Climate shows a significance of 0.145 with a path coefficient of 0.145. The p value obtained is <0.05. Principal Leadership, Academic Supervision simultaneously have a significant effect on Teacher Performance, indicated by the calculated F value of 270.570> F table (2.629). The contribution of all exogenous variables to teacher performance is 68.4%. Based on the results of this study, it can be concluded that principal leadership, academic supervision, and school climate simultaneously affect teacher performance in Semarang City.